Tourism and Regional Development – the Case of Romania - Gina-Ionela Butnaru; Clara Minut (CES Working Papers, 2012)
The policies regarding regional development in the last years took tourism more and more into account, as a strategic sector for the assurance of a dynamic economic growth of regions with an important tourism potential. Consequently, we intend to analyse the implications of the North-East Regional Development Agency in the development of Romanian tourism in the present socio-economic context, both at regional and at national level.
Keywords: M19; O22; R19; R58; 330; regional development; tourism; North-East Regional Development Agency; Romania Romania